2016
DOI: 10.3855/jidc.7997
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and multidrug resistance of Escherichia coli from community-acquired infections in Lagos, Nigeria

Abstract: Introduction: The emergence of multidrug resistance (MDR; resistance to ≥ 2 more antimicrobials) in Escherichia coli is of concern due to complications encountered in treatment. Methodology: In this study, prevalence, antimicrobial resistance, and genetic characteristics of MDR community isolates of E. coli from Lagos, Nigeria were determined. Urine and stool samples were obtained from outpatients attending Lagos State hospitals and from animal handlers in abattoirs, poultries, and open markets, from December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
31
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 80 publications
(90 reference statements)
11
31
3
Order By: Relevance
“…All isolates had at least one extended-spectrum β-lactamase (ESBL) resistance gene detected. The isolates also harbored genes conferring resistance to aminoglycosides, tetracycline, trimethoprim, sulfonamides, fluoroquinolones, and chloramphenicol, consistent with their reported phenotypes ( 15 , 16 ). The detection of circulating antibiotic resistance genes in bacteria from humans and food animals using genome sequencing is useful in predicting emerging resistance, especially in underfunded countries.…”
Section: Genome Announcementsupporting
confidence: 78%
See 1 more Smart Citation
“…All isolates had at least one extended-spectrum β-lactamase (ESBL) resistance gene detected. The isolates also harbored genes conferring resistance to aminoglycosides, tetracycline, trimethoprim, sulfonamides, fluoroquinolones, and chloramphenicol, consistent with their reported phenotypes ( 15 , 16 ). The detection of circulating antibiotic resistance genes in bacteria from humans and food animals using genome sequencing is useful in predicting emerging resistance, especially in underfunded countries.…”
Section: Genome Announcementsupporting
confidence: 78%
“…In order to effectively treat these infections, it is important to understand the mechanisms of resistance in E. coli . As a first step in this study, we report here the draft genome sequences of nine MDR E. coli strains isolated from outpatients ( n = 5), animal handlers ( n = 1), and chickens ( n = 3) in Lagos, Nigeria, in 2013 ( 15 , 16 ).…”
Section: Genome Announcementmentioning
confidence: 99%
“…This may be explained by either variation in the occurrence of ESBLs across regions/states or the rising trend of ESBLs in Nigeria. This study and other studies from Nigeria are showing low levels of resistance of E. coli to piperacillin-tazobactam and carbapenems (Adenipekun et al, 2016, Iliyasu et al, 2016, underscoring the need to strengthen antimicrobial stewardship programs to preserve them as potential therapeutic options now and for future generations.…”
Section: Discussionmentioning
confidence: 57%
“…There is an need to evaluate simple, reliable and cost effective epidemiological laboratory tools in resource limited countries such as those in Africa, where limited information exist regarding the population structure of ExPEC. Previous studies from Lagos and Oyo states in Nigeria have revealed presence of E. coli ST131, but did not determine the presence of other clones among ExPEC (Adenipekun et al, 2016, Aibinu et al, 2012, Inwezerua et al, 2014. A study was designed to determine antimicrobial susceptibility patterns and the population structure of ExPEC isolates (ST/fimH types) in a tertiary care center from North-eastern Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial resistance is mostly attributed to the misuse of antimicrobial drugs as therapies, prophylactics and as growth promoters (Frye and Jackson 2013;Adenipekun et al 2016). Data available thus far has indicated that expression of antimicrobial resistance occurs either due to chromosomal mutations or after acquisition of resistance genes carried on mobile genetic elements, mostly plasmids (Blair et al 2015;Stratev and Odeyemi 2016).…”
Section: Introductionmentioning
confidence: 99%